Electron-conformational rearrangement in nanocomposites films of poly-N-epoxypropylcarbazole with fullerenes C₆₀ - Olasyuk, O.P.; Dmytrenko, O.P.; Kulish, M.P.; Zabolotnyy, M.A.; Borodina, H.Y.; Busko, T.O. (Functional Materials, 2017)
Optical absorption spectra, optical conductivity, refractive index n, extinction coefficient k and photoluminescence in nanocomposite films of poly-N-epoxypropylcarbazole (PEPC) with 0,7; 1,35; 2,5 and 4 wt.% of C₆₀ molecules were studied. Substantial restructuring of these spectra with changing the fullerene C₆₀ content was established not only in the intrinsic absorption, but also within the energy gap. Reducing the energy distance between states S₁ and T₁ with increasing concentration of C₆₀ molecules was showed, as well as the appearance of additional broad structureless bands with a maximum near 700 nm in the long-wave photoluminescence spectrum. Restructuring of the spectra is associated with electron-conformational changes caused by appearance of the donor-acceptor interaction between components in the films PEPC-C₆₀ due to formation of the complexes with charge transfer (CCT) in them.